Novel Mixed Complexes Derived from Benzoimidazolphenylethanamine and 4-(Benzoimidazol-2-yl)aniline: Synthesis, Characterization, Antibacterial Evaluation and Theoretical Prediction of Toxicity - Aroua, Lotfi M. (Asian Journal of Chemistry, 2020)
Benzoimidazolphenylethanamine (BPE) has been synthesized using condensation reaction from o-phenyldiamine and L-phenylalanine. Some metal complexes have been synthesized from 4-(benzoimidazol-2-yl)aniline, benzoimidazolylphenylethanamine and cadmium(II), tin(II), copper(II) and nickel(II) metal in a molar ratio (1:1:1). All new metal complexes were characterized by spectroscopic data of FTIR, UV-visible electronic absorption, X-ray powder diffraction and thermal analysis. Spectra analysis of the mixed metal complexes showed the coordination of ligands to the metal ions via nitrogen atoms. The XRD powder showed that metal complexes have a monoclinic system. The preliminary tested in vitro antibacterial activities of Sn(II) complex was assayed against four bacterial isolates namely Micrococcus luteus, Staphylococcus aureus as Gram-positive, Pseudomonas aerugmosa and Escherichia coli.